Sensory, Microbiological and Chemical Changes in Vacuum‐Packaged Blue Spotted Emperor (Lethrinus sp), Saddletail Snapper (Lutjanus malabaricus), Crimson Snapper (Lutjanus erythropterus), Barramundi (Lates calcarifer) and Atlantic Salmon (Salmo salar) Fillets Stored at 4°C. Issue 3 (15th December 2015) - Fuentes‐Amaya, Luisa Fernanda; Munyard, Steve; Fernandez‐Piquer, Judith; Howieson, Janet
Abstract: Quality assessment of finfish fillets during storage is important to be able to predict the shelf life of the fresh product during distribution. Microbial, chemical (pH, TMA, and TVB‐N), and sensory (Quality index assessment QIA, Torry scheme) changes in vacuum‐packaged blue‐spotted emperor ( Lethrinus sp), saddletail ( Lutjanus malabaricus ), crimson snapper ( Lutjanus erythropterus ), barramundi ( Lates calcarifer ), and Atlantic salmon ( Salmo salar ) fillets stored at 4°C were evaluated for 5 days. Microbiological study included evaluation of TVC (total viable counts), total psychrotrophic organisms, and H2 S‐producing bacteria. Numbers increased during storage time and reached an average of 8.5, 8.5, and 9.2 log10  cfu/g, respectively, for the five different fish species. These levels were above accepted microbiological limits for fish fillets. Although the sensory analyses showed a decrease in quality, none of the finfish fillets were considered unacceptable at the end of the storage trial. Chemically, there was a slight pH increase, but trimethylamine (TMA) levels remained low. However, total volatile basic nitrogen (TVB‐N) levels increased over time, reaching levels above 35 mg/100 g for blue spotted emperor, saddletail snapper, and crimson snapper by the end of the storage period. Results show that the deterioration of finfish fillet quality is a complex event of biochemical, sensory, and microbial factors, and multiple analyses may be required to define acceptability. Abstract : Finfish fillet quality is a complex event of biochemical, sensory, and microbial factors, which requires of multiple analyses to define acceptability.